Anti-tRNA synthetase syndrome interstitial lung disease: A single center experience. (January 2022) - Wilfong, Erin M.; Young-Glazer, Jennifer J.; Sohn, Bret K.; Schroeder, Gabriel; Annapureddy, Narender; Gillaspie, Erin A.; Barnado, April; Crofford, Leslie J.; Dudenhofer, Rosemarie Beckford
Abstract: Background: Recognition of Anti-tRNA synthetase (ARS) related interstitial lung disease (ILD) is key to ensuring patients have prompt access to immunosuppressive therapies. The purpose of this retrospective cohort study was to identify factors that may delay recognition of ARS-ILD. Methods: Patients seen at Vanderbilt University Medical Center between 9/17/2017-10/31/2018 were included in this observational cohort. Clinical and laboratory features were obtained via chart abstraction. Kruskal-Wallis ANOVA, Mann-Whitney U, and Fisher's exact t tests were utilized to determine statistical significance. Results: Patients with ARS were found to have ILD in 51.9% of cases, which was comparable to the frequency of ILD in systemic sclerosis (59.5%). The severity of FVC reduction in ARS (53.2%) was comparable to diffuse cutaneous systemic sclerosis (56.8%, p = 0.48) and greater than dermatomyositis (66.9%, p = 0.005) or limited cutaneous systemic sclerosis (71.8%, p = 0.005). Frank honeycombing was seen with ARS antibodies but not other myositis autoantibodies. ARS patients were more likely to first present to a pulmonary provider in a tertiary care setting (53.6%), likely due to fewer extrapulmonary manifestations. Only 33% of ARS-ILD were anti-nuclear antibody, rheumatoid factor, or anti-cyclic citrullinated peptide positive. Patients with ARS-ILD had a two-fold longer median time to diagnosis compared to other myositis-ILD patients (11.0 months, IQR 8.5–43 months vs. 5.0 months, IQR 3.0–9.0 months, p = 0.003). Conclusions: ARS patients without prominent extra-pulmonary manifestations are at high risk for not being recognized as having a connective tissue disease related ILD and miscategorized as usual interstitial pneumonia/idiopathic pulmonary fibrosis without comprehensive serologies. Highlights: Isolated interstitial lung disease is common in anti-tRNA synthetase syndromes. Diagnostic delays in anti-tRNA synthetase syndrome patients are common. Common autoantibodies often fail to detect anti-tRNA synthetase syndrome lung disease.